Analisis Kinerja Keuangan Bank Syariah Dengan Menggunakan Rasio Likuiditas, Solvabilitas dan Efisiensi - Nopiantika, Tiara; Asnaini, Asnaini; Indra, Yetti Afrida (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
This study aims to determine the financial performance of Bank Muamalat Indonesia using liquidity, solvency and efficiency. this type of descriptive research with a quantitative approach. using secondary data, namely the annual financial statements of Bank Muamalat for the 2017-2020 period. The analysis technique of this research is Microsoft Excel software. The results showed that liquidity using the quick ratio and cash ratio of Bank Muamalat Indonesia's performance was not healthy, while using the loan to deposit ratio and asset to loan ratio the performance was said to be healthy. Solvency financial performance using the primary ratio and capital ratio is said to be healthy, while using the second risk ratio is not healthy. Financial performance with efficiency using cost of funds and an unhealthy levereg ratio, the higher the deposit interest rate, the higher the burden on the bank and the higher the risk of the company failing to pay creditors.